EFEKTIVITAS PEMBERIAN EKSTRAK JAHE MERAH (ZINGIBER OFFICINALE) TERHADAP JUMLAH SEL FIBROBLAS DALAM PROSES PENYEMBUHAN ULKUS PADA MUKOSA MULUT TIKUS PUTIH JANTAN (RATTUS NORVEGICUS) - Prima Agusmawanti (Faculty of Dentistry, Universitas Islam Sultan Agung, 2016)
Background: In the wound healing process there are a variety of processes, including the most important are fibroplasia process that has a very important role in the wound healing process. Red ginger (Zingiber officinale) contains active ingredients include a mixture of components of essential oils and resins that oleoresin which has anti-inflammatory effects. The aim is determine the effect of red ginger extract against the number of fibroblasts in healing ulcers on the oral mucosa white male rats (Rattus norvegicus)Method: Samples using 24 male rats 2-3 months of age and body weight of 120-200 grams. Mandibular labial mucosa injured mice using H2O2 solution for 2x1 days. The samples were divided into 4 groups, where each group each of 4individuals: group 1 without any treatment, group 2 was treated application ginger gel extract 4%, group 3 was given treatment application ginger gel extract 8% and group 4 treated with applications aloclair gel. On the fourth day after the injury,the rats were decapitated, then do making preparations for histology to count the number of fibroblast cells.Result: The results Oneway ANOVA p value <0.05 and post Hoc Test LSD p value <0.05 which means that the extract of red ginger significantly affects the number of fibroblast cells and between groups have significant differencesConclusion: Extract red ginger gel is effective against the number of fibroblasts in healing ulcers on the oral mucosa white male rats.